School Leadership in Global Perspective: A Study of the Influence of Organizational Culture, Ability, and Motivation Based on Geoleadership Model towards Leadership Capacity in Realizing Intelligent School at Catholic Junior High Schools in West Java, Indonesia - Iskandar, Sherly Iliana (EDUCARE, 2012)
ABSTRACT: Indonesia is a part of the world in the process of globalization. Ready or not, Indonesia is involved in the changing of competition paradigm, from material to knowledge competition. This demands the government and educational institution to be ready with strategy and global vision in taking needed steps for adjustments and changes. This quantitative study on 130 Catholic Junior High Schools Leaders in West Java area in Indonesia, about the influence of organizational culture, ability, and motivation based on geoleadership model towards leadership capacity, is conducted in responding to the radical impact of globalization to all aspect of life, including education in Indonesia. It is urgently needed to find a model of educational leadership to create intelligent school as an appropriate school for this situation. The result of the study showed that ability has the strongest influence (48.23%) to leadership capacity, followed by motivation (32.37%), and organizational culture (16.34%). Recommendation for Catholic Junior High Schools Leaders in West Java area in Indonesia is improving ability, motivation by training, and improving organizational culture by creating a conducive working climate to develop leadership capacity in realizing intelligent school.KEY WORDS: Organizational culture, ability, motivation, geoleadership model, leadership capacity, and intelligent school.About the Author: Dr. Ir. Sherly Iliana Iskandar is a Cum Laude Ph.D. Graduan of the Educational Administration Program at School of Postgraduate UPI (Indonesia University of Education), Jalan Dr. Setiabudhi No.229 Bandung 40154, West Java, Indonesia. She can be reached at: shc@melsa.net.idHow to cite this article? Iskandar, Sherly Iliana. (2012). âSchool Leadership in Global Perspective: A Study ofÂ  the Influence of Organizational Culture, Ability, and Motivation Based on Geoleadership Model towards Leadership Capacity in Realizing Intelligent School at Catholic Junior High Schools in West Java, Indonesiaâ in EDUCARE: International Journal for Educational Studies, Vol.4(2) February, pp.137-154. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (December 25, 2011); Revised (January 29, 2012); and Published (February 17, 2012).